Evaluation of the Landfill Storage Capacity in Slovakia, Compared to the EU Situation - Zuzana Šimková; Marcela Taušová; Katarína Čulková; Peter Tauš; Danylo Shyp; David Krasniči; Simona Novotná (Recycling, 2024)
The circular economy and efficient use of resources gained importance in the context of sustainable development. The paper aims to evaluate the development of landfilling in Slovakia. The next goal is to assess the trend in compared with the EU’s situation. The presented research presents a continuation of previous research in the area of waste recycling in Slovakia, pointing to the waste and landfilling, which is deserving of analysis from a long-term perspective. The research is carried out via data collection at the EU level by recording continuously published values. The paper’s results are processed in statistical software. Considering regional development, landfilling in Slovakia is followed up according to the geographical units of the entire country. The results shown here show that a higher recycling capacity is required and Slovakia should decrease its level of landfill. Such results can be used in the waste treatment area, protection of the living environment and sustainable development of regions.